PTU-024 Photometric stereo reconstruction for surface analysis of mucosal tissue. (22nd June 2015) - Poullis, A; Groves, C; Slabaugh, G; Emrith, K; Smith, M
Abstract : Introduction: The American Society of Gastroenterology endoscopy led Preservation and Incorporation of Valuable endoscopic Innovations initiative has identified real time polyp detection diagnosis as one of the next major technology-driven changes in endoscopy. 1 We have recently described a novel photometric stereo (PS) imaging sensor for endoscopy imaging in a porcine model. 2 Following image acquisition, reconstruction of the surface data is necessary to calculate the shape index (SI) to identify regions that are locally spherical, suggestive of polyps to aid polyp detection. Method: Using a porcine gut model, photometric images were captured using a six-light source PS setup as previously described. 2 Surface analysis of the obtained surface data was performed: Derivatives of the height fields arranged on a square lattice were calculated using finite differences, and used to characterise the differential geometry using the principal curvatures. 3 Surface measures analysis: for each point on the surface, the shape index (SI) was computed and used to measure the local shape: SI = 1/2 – 1/π tan−1 ((K1+K2)/(K1-K2)) Results: Conclusion: Using a novel PS image acquisition 3D reconstruction was obtained on colonic mucosa. We observe that the recovered 3D surface retains the surface geometry in the captured areas and important structural information at a fine level of detail, even in the presence of numerous specular reflections. This is highly significant for automated processing and analysis of surface abnormalities. Disclosure of interest: None Declared. References: Rex, et alet al. Gastrointest Endosc 2011;73 :419–22 Poullis, et alet al. Gut 2014;63 (Suppl 1):A46 do Carmo M. Differential geometry of curves and surfaces . Prentice Hall, 1976, ISBN:0132125897